Civil Society’s Contributions and Challenges in the Development of Business and Human Rights Policy in Indonesia - Wahyu Wagiman; Mutia Salsabila (Universitas Airlangga, 2022)
Civil society greatly contributes to encouraging the adoption of the United Nations Guiding Principles on Business and Human Rights (UNGPs) into practice and legislation in Indonesia. This contribution can be seen from the various policies and actions taken by the Indonesian government in referring to the UNGPs when forming policies related to human rights or the operation of companies in Indonesia. This research aims to serve as a database and as consideration for civil society in Indonesia to advocate for business and human rights issues, especially the issues related to actions taken by civil society to influence Indonesian governmental policies and the challenges faced by civil society. As such, civil society will be able to measure the urgency of intervention in policymaking related to business and human rights. This research was conducted using qualitative and comparative approaches. The qualitative approach was carried out through studies of literature, both primary and secondary. The comparative approach aimed to analyse and compare two or more objects based on a theoretical framework. The comparison results can be in the form of similarities or differences in the aspects studied. This research process pays attention to certain sensitive contexts that require a context-sensitive approach.